Analysis of Application of Fuzzy Grid Partition on Mamdani Method Fuzzy Inference System - Marbun, Murni; -, Sandhuri; -, Aishwarya (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2022)
The Mamdani method has been widely used for various control devices, which is the beginning of fuzzy technology and has the advantage of being able to express concepts that are difficult to formulate and the use of fuzzy membership functions in making objective observations of subjective values, making it easier to make decisions that are full of uncertainty. The Mamdani method has also been widely used for various optimization problems. This study produces new findings on the analysis of the application of fuzzy grid partition on the fuzzy inference system of the Mamdani method for the issue of optimizing the amount of production of a food product. The research stage begins with determining the number of partitions that will form a grid structure. The grid formed from the combination of relations between each partition will have the potential to develop rules. Based on the results of the analysis, determining the amount of production using the Mamdani method produces a smaller amount of production but produces stock output that is not within the specified stock limit, while the application of fuzzy grid partition in the Mamdani method has a higher and correct amount of product because it produces stock output that is at the specified stock limit